2017
DOI: 10.1590/2359-3997000000314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biliopancreatic diversion on sleep quality and daytime sleepiness in patients with obesity and type 2 diabetes

Abstract: Objective: The poor quality of sleep and the deprivation thereof have been associated with disruption of metabolic homeostasis, favoring the development of obesity and type 2 diabetes (T2DM). We aimed to evaluate the influence of biliopancreatic diversion (BPD) surgery on sleep quality and excessive daytime sleepiness of obese patients with T2DM, comparing them with two control groups consisting of obese and normal weight individuals, both normal glucose tolerant. Subjects and methods: Forty-two women were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
0
0
3
Order By: Relevance
“…This is because patients stated that the recommended instructions about sleep and rest after bariatric surgery in the module was easy and simple to applied and followed. This enhances quality, duration of sleep and improves obstructive sleep apnea, and body posture.This result is consistent with Mello et al who stated that bariatric surgery have demonstrated improvement in sleep disorders in people after surgery due to the impact of weight reduction [19] .…”
Section: Discussionsupporting
confidence: 92%
“…This is because patients stated that the recommended instructions about sleep and rest after bariatric surgery in the module was easy and simple to applied and followed. This enhances quality, duration of sleep and improves obstructive sleep apnea, and body posture.This result is consistent with Mello et al who stated that bariatric surgery have demonstrated improvement in sleep disorders in people after surgery due to the impact of weight reduction [19] .…”
Section: Discussionsupporting
confidence: 92%
“…Por outro lado, dada a relevância do sono na homeostase metabólica e a associação entre a qualidade do sono, obesidade e DM2, um estudo feito pelo Laboratório de Investigação em Metabolismo e Diabetes (LIMED), em parceria com o Departamento de Cirurgia Bariátrica e Metabólica, ambos provenientes da Universidade Estadual de Campinas (Unicamp), avaliaram a sonolência diurna excessiva e a qualidade do sono em indivíduos obesos com DM2, comparandoos com dois grupos de controle, 42 mulheres na pré-menopausa que compuseram os seguintes grupos: 11 voluntárias com peso normal (LeanC) (IMC = 23,2 kg / m 2 ) com tolerância normal a glicose (NGT); 13 voluntárias obesas (ObeseC) (IMC = 35 ± 5 kg / m 2 ) com NGT; 18 voluntárias obesas (T2DMObese) (IMC = 35 ± 5 kg / m 2 ) com DM2 submetidas à cirurgia de Desvio Bileopancreático (DBP) (MELLO et al, 2017).…”
Section: Seguimento De Pacientes Com Sonolência Diurna Excessiva Em C...unclassified
“…A extremidade proximal do íleo foi anastomosada de 80 a 120 cm de distância do válvula ileocecal. O comprimento total de absorção intestinal foi reduzido para 280-300 cm, cujos 80-120 cm foram chamados canal comum final (MELLO et al, 2017).…”
Section: Seguimento De Pacientes Com Sonolência Diurna Excessiva Em C...unclassified
See 1 more Smart Citation